Vigilantes, anti-drug movements, and community empowerment : a Dublin case study - Nugent, Erin S. (Trinity College (Dublin, Ireland). Department of Sociology, 2006)
The Dublin anti-drug movement was a response to the escalation of the overt heroin problem in inner-city areas. In the early 1980’s, Concerned Parents Against Drugs (CPAD) became a citywide network whose intention was to empower local communities to tackle the problem themselves. The movement’s ideals surfaced again in the mid-1990’s when the Coalition of Communities Against Drugs (COCAD) formed to address the second wave of the heroin epidemic in disadvantaged areas. However, one article by Bennett (1988) on the surveillance techniques of CPAD remains the only published research on the movement. Short references to CPAD also exist in various books which examine community, crime, or drug-related issues. These mention the anti-drug movement as a ‘social’ movement which exercised social control in inner-city areas. CPAD was also frequently presented as a ‘vigilante’ movement in the media during the 1980’s, as was COCAD a decade later. Furthermore, the existing literature and early interviews indicated that the anti-drug movement was closely associated with two agencies: Sinn Fein and the Inner-City Organisations Network (ICON).
Keywords: Sociology, Ph.D.; Ph.D. Trinity College Dublin